1997
DOI: 10.1021/jp971298r
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Yield of NO3 from Peroxyacetyl Nitrate Photolysis

Abstract: Peroxyacetyl nitrate (PAN) vapor was photolyzed at 248 nm and the NO3 photoproduct was detected by laser-induced fluorescence. The quantum yield for the production of NO3 was determined by comparison to N2O5 photolysis data taken under identical experimental conditions. Contributions to the observed laser induced fluorescence were found to arise from excited-state photoproducts such as NO2*. The excited-state fluorescence contributions were investigated, and a data analysis methodology was established to minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 22 publications
5
31
0
Order By: Relevance
“…Numerous experimental studies , have shown that the thermal decomposition of PAN occurs only via the NO 2 producing channel (nitrate O−N bond cleavage) with no contribution from the NO 3 producing channel (peroxy O−O bond cleavage) even though the channels are predicted to be nearly isoenergetic. , It has been argued that the thermal decomposition via R1a is favored over R1b because R1a dissociation proceeds without a barrier; however, the thermochemistry of PAN, CH 3 C(O)O 2 , and CH 3 C(O)O is poorly defined, so the actual reaction enthalpies have uncertainties of at least 20 kJ mol -1 . Additionally, the 248 nm photodissociation experiments performed by Mazely, Friedl, and Sander , demonstrated significant quantum yields for both channels, φ (R1a) = 0.89 ± 0.09 and φ (R1b) = 0.30 ± 0.10 so that, if there is a barrier to dissociation via R1b, it is surmountable at fairly low energies.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous experimental studies , have shown that the thermal decomposition of PAN occurs only via the NO 2 producing channel (nitrate O−N bond cleavage) with no contribution from the NO 3 producing channel (peroxy O−O bond cleavage) even though the channels are predicted to be nearly isoenergetic. , It has been argued that the thermal decomposition via R1a is favored over R1b because R1a dissociation proceeds without a barrier; however, the thermochemistry of PAN, CH 3 C(O)O 2 , and CH 3 C(O)O is poorly defined, so the actual reaction enthalpies have uncertainties of at least 20 kJ mol -1 . Additionally, the 248 nm photodissociation experiments performed by Mazely, Friedl, and Sander , demonstrated significant quantum yields for both channels, φ (R1a) = 0.89 ± 0.09 and φ (R1b) = 0.30 ± 0.10 so that, if there is a barrier to dissociation via R1b, it is surmountable at fairly low energies.…”
Section: Introductionmentioning
confidence: 97%
“…11,12 It has been argued that the thermal decomposition via R1a is favored over R1b because R1a dissociation proceeds without a barrier; 4 however, the thermochemistry of PAN, CH 3 C(O)O 2 , and CH 3 C(O)O is poorly defined, so the actual reaction enthalpies have uncertainties of at least 20 kJ mol -1 . Additionally, the 248 nm photodissociation experiments performed by Mazely, Friedl, and Sander 16,17 demonstrated significant quantum yields for both channels, φ(R1a) ) 0.89 ( 0.09 and φ(R1b) ) 0.30 ( 0.10 so that, if there is a barrier to dissociation via R1b, it is surmountable at fairly low energies.…”
Section: Introductionmentioning
confidence: 97%
“…Other, minor NO 3 sources include the reaction of OH with HNO 3 47 and the photolysis of some organic nitrates. 48,49 The recommended rate of reaction (R1.1) at room temperature is k 1.1 = 3.2 Â 10 À17 cm 3 molecule À1 s À1 . The reaction rate is temperature dependent, slowing down considerably at lower temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the generation and global distribution of PAN in the atmosphere is well understood 4–7. Also its spectroscopic and photochemical properties have been well characterized 8–16 and several papers have been published about its thermal decomposition 17–26.…”
Section: Introductionmentioning
confidence: 99%